(untitled) (Scientific journal of the Fergana State University, 2024)
The lexical-semantic features of the language of the works, morphological structure, syntactic structure, lexical language units were determined by linguists, and scientific monographs and articles were published on them. The article presents ideas on the study of the lexical layers of the “Navoi” novel’s language.